The Medical Education Partnership Initiative: Strengthening Human Resources to End AIDS and Improve Health in Africa. (November 2019) - Kilmarx, Peter H.; Katz, Flora; Razak, Myat Htoo; Palen, John; Cheever, Laura W.; Glass, Roger I.
Abstract : Faced with a critical shortage of physicians in Africa, which hampered the efforts of the U.S. President's Emergency Plan for AIDS Relief (PEPFAR), the Medical Education Partnership Initiative (MEPI) was established in 2010 to increase the number of medical graduates, the quality of their education, and their retention in Africa. To summarize the accomplishments of the initiative, lessons learned, and remaining challenges, the authors conducted a narrative review of MEPI—from the perspectives of the U.S. government funding agencies and implementing agencies—by reviewing reports from grantee institutions and conducting a search of scientific publications about MEPI. African institutions received 11 programmatic grants, totaling 100 million in PEPFAR funds, to implement MEPI from 2010 to 2015. The National Institutes of Health (NIH) provided an additional 8 linked and pilot grants, totaling 30 million, to strengthen medical research capacity. The 13 grant recipients (in 12 countries) partnered with dozens of additional government and academic institutions, including many in the United States, forming a robust community of practice in medical education and research. Interventions included increasing the number of medical school enrollees, revising curricula, recruiting new faculty, enhancing faculty development, expanding the use of clinical skills laboratories and community and rural training sites, strengthening computer and telecommunications capacity, and increasing e-learning. Research capacity and productivity increased through training and support. Additional support from NIH for faculty development, and from PEPFAR for health professions education and research, is sustaining and extending MEPI's transformative effect on medical education in select African sites.